Analisis Korelasi Keterampilan Metakognitif dengan Hasil Belajar Kimia Siswa - Priantiningtias, Febri Nanda; Azizah, Utiya (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
The research aimed to analyze the correlation between metacognitive skills with students' chemistry learning outcomes. The research method used is descriptive correlational with data collection techniques through observation to measure the implementation of learning models, test to measure the students' achievement and metacognitive skills, and a questionnaire to measure students' Metacognitive Awareness Inventory (MAI). This research used a simple random sampling technique of 31 students from XI MIPA 1. The data analysis technique was the percentage, n-gain, analysis of normality by Shapiro-Wilk, the correlation analysis by Product Moment Pearson and Regression Linear using the IBM SPSS Statistics 21 application. The result showed that 1) the average percentage implementation of the learning models respectively at meetings 1 and 2 was 96.9% and 97.8% respectively with very good category, 2) metacognitive skills trained were conveyed very well, supported by the average MAI that is good and the average of N-Gain percentage of metacognitive skills and students' achievement were categorized in the high category, 3) had a positive correlation with a coefficient correlation value of 0,952 (there is a high relationship between variables), and R square of 0,907, and, 4) the linear formula equation is y = -24,922 + 1,223X.